Fit fürs Klassenzimmer Konzeption und Evaluation eines Resilienzförderungsprogramms für Lehramtsstudierende - Görich, Katja (Studien zur Professionsforschung und Lehrerbildung, 2019)
As part of this work, the RefueL programme was developed and positively evaluated to promote the resilience of student teachers in the run-up to the practical semester. With the programme, the professional and didactic career preparation of prospective teachers during their studies was supplemented by an offer for the training of psychological and social resilience. The developed programme consists of five modules on the topics of resilience in the teaching context, shaping social relationships, well-being, setting goals and solving problems, and regulating emotions. These modules contain a variety of practical exercises to promote resilience and are implemented in a face-to-face setting. A longitudinal control group design was chosen for the evaluation. Among other things, hierarchical regressions were calculated. The programme proved to be effective at four different evaluation levels. Significantly, participants showed lower burnout symptoms, more positive affect and higher teaching-related self-efficacy expectations after the practical semester than students in the control group, after controlling for baseline values. The study results speak in favour of anchoring resilience promotion programmes in the curriculum at universities with practical semesters and thus contributing to the professionalisation of prospective teachers.